2012
DOI: 10.1371/journal.pone.0047193
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of p15INK4b and Expression of ANRIL on Chromosome 9p21 Are Associated with Coronary Artery Disease

Abstract: BackgroundGenome-wide association studies have identified that multiple single nucleiotide polymorphisms on chromosome 9p21 are tightly associated with coronary artery disease (CAD). However, the mechanism linking this risk locus to CAD remains unclear.Methodology/Principal FindingsThe methylation status of six candidate genes (BAX, BCL-2, TIMP3, p14ARF, p15INK4b and p16INK4a) in 205 patients and controls who underwent coronary angiography were analyzed by quantitative MethyLight assay. Rs10757274 was genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 48 publications
0
55
0
Order By: Relevance
“…One of the major mechanisms to down-regulate expression of a gene is methylation of a cytosine and guanine rich area, called CpGislands, in the promoter region of the gene [9]. A few studies have indicated that DNA promoter methylation of certain genes is responsible for the susceptibility of CHD [10][13].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major mechanisms to down-regulate expression of a gene is methylation of a cytosine and guanine rich area, called CpGislands, in the promoter region of the gene [9]. A few studies have indicated that DNA promoter methylation of certain genes is responsible for the susceptibility of CHD [10][13].…”
Section: Introductionmentioning
confidence: 99%
“…29 Cross-sectionally, hypermethylation of PLA2G7 was associated with coronary heart disease (CHD) among females 30 and hypermethylation of a locus on 9p21, a region of robust genetic associations with CVD, was more prevalent among coronary artery disease cases in a Chinese population. 51 …”
Section: Candidate Gene Methylation Studiesmentioning
confidence: 99%
“…Cytokines' haplotypes comprising of CAD-susceptible alleles could significantly affect the disease pathophysiology by up-regulating the inflammatory markers expression. Furthermore, evidence shows that methylation of P15INK4B appears to be involved in the pathogenesis of CAD [33]. This suggests that promoter region methylation is another factor that may influence gene expression.…”
Section: Role Of Cytokines Signaling Pathway In Cadmentioning
confidence: 99%